Thoracic Spinal Anesthesia (TSA) in Patients with Congestive Heart Failure and Pleural Effusion Undergoing Breast Tumor Surgery: A Case Report - Aryasena Andhika Wiedjaja; Muhammad Rizqhan (JAI (Jurnal Anestesiologi Indonesia))
Background: Thoracic spinal anesthesia (TSA) is a regional anesthesia technique that can serve as an alternative to general anesthesia, particularly for patients with cardiovascular and respiratory comorbidities, to reduce adverse effects and provide a more effective procedure.